Fluconazole-induced acute generalized exanthematous pustulosis - Vito Di Lernia; Cinzia Ricci (Wolters Kluwer Medknow Publications, 2015)
Acute generalized exanthematous pustulosis (AGEP) is a severe cutaneous adverse reaction and is usually caused by drugs. It is characterized by fever and acute, extensive occurrence of disseminated sterile pustules, accompanied by fever, malaise and peripheral blood leucocytosis. There have been several reports to date of AGEP following exposure to antifungals. In particular, terbinafine is included in the list of the agents conferring the highest risk of AGEP. The authors report the case of a 70-year-old male patient who developed AGEP shortly after commencing treatment with fluconazole, which has been reported in association with AGEP in a single case report. To our knowledge, this is the first reported case of AGEP associated with positive fluconazole patch test.